Strategies to Improve English Reading Comprehension - Lailan Fadila; Sakinah Amaliyah Dalimunthe; Nursakinah Siagian (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study explores strategies aimed at enhancing English reading comprehension. With the backdrop of a complex information era, where proficient reading skills are crucial for accessing and applying information, the study focuses on interactive reading techniques, vocabulary acquisition, prior knowledge activation, and reading fluency as key components. The research adopts a literature review approach, synthesizing findings from existing studies to identify effective strategies. The primary objective is to ascertain which methods best contribute to improved reading comprehension in educational settings. Findings indicate that interactive techniques such as group discussions and role-playing, coupled with explicit vocabulary instruction and prior knowledge activation strategies, significantly enhance comprehension levels. Furthermore, fostering reading fluency through repeated reading and guided oral sessions positively correlates with improved comprehension abilities. The study concludes that a holistic approach integrating these strategies is essential for developing proficient readers who can engage effectively with diverse texts and contexts.